Pendidikan hukum kepada pengusaha makanan khas/tradisonal dalam melakukan pendaftaran merek di Desa Pangkalan Jambi Kecamatan Bukit Batu Kabupaten Bengkalis - Ulfia Hasanah; Firdaus Firdaus; Setia Putra; Samariadi Samariadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
One of the growing industrial activities in Bengkalis is the business in the field of production of Traditional / Traditional Foods. Currently known for some typical / traditional foods that are in demand, including dodol, Bolu, Onion chips and others. But there are entrepreneurs of the products sold there who have not registered their brands. Whereas the consequences of not registering a trademark enable the occurrence of counterfeiting or unfair competition which is also greatly felt by business actors and protection of the trademark is also very necessary. The purpose of community service activities is to provide socialization and understanding to the public about the importance of trademark registration and trademark registration procedures. This activity can also increase knowledge competence, skills, community motivation, and role in trademark registration. The importance of providing assistance to the community in protecting the products they produce. The initial activity was initiated by taking information from the community about food products in the Pangangalan Jambi village. Data collection techniques carried out by interview, observation and document analysis. The existence of local products produced by the community in Pangkalan Jmabi Village has made this village a choice in community service activities. Community service activities carried out through personal and community approaches. The results of community service activities showed the enthusiasm of the community attending a series of activities, and the active role of the community was quite good. Activities carried out continuously and continuously have a positive impact on community growth and development.